2016
DOI: 10.2174/1389201016666150907113435
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Molluscan Hemocyanins from Helix and Rapana Snails

Abstract: For the first time the antimicrobial activities of hemocyanins from the molluscs Rapana venosa (RvH) and Helix aspersa (HaH) have been tested. From the hemolymph of the garden snail H. aspersa one structural subunit (βc-HaH ) and eight functional units (FUs, βc-HaH-a to βc-HaH-h) were isolated, and their N-terminal sequences and molecular weights, ranging between 45 and 65 kDa, determined. The antimicrobial test of the hemocyanins against different bacteria showed that only two FUs from Rapana, RvH1-b and RvH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 0 publications
0
54
0
Order By: Relevance
“…HMC is the main protein component of hemolymph, and is found in both hemocyte and plasma. The function HMC in invertebrate is not only as a respiratory protein via oxygen transport, but it has also been strongly associated with different immunological processes [6066]. HMC has been shown to participate in multiple roles of the immune response including phenoloxidase activity [6164], antiviral [65] and antimicrobial activity [66].…”
Section: Discussionmentioning
confidence: 99%
“…HMC is the main protein component of hemolymph, and is found in both hemocyte and plasma. The function HMC in invertebrate is not only as a respiratory protein via oxygen transport, but it has also been strongly associated with different immunological processes [6066]. HMC has been shown to participate in multiple roles of the immune response including phenoloxidase activity [6164], antiviral [65] and antimicrobial activity [66].…”
Section: Discussionmentioning
confidence: 99%
“…Although diverse antimicrobial and antiviral properties of mollusc Hc oligomers and several FUs have been noted [21, 184–186], mollusc Hc-derived peptides have received little attention. An interrogation of whelk ( Rapana venosa ) hemolymph led to the identification of a peptide with sequence similarities to a conserved motif at the N-terminus of many Hc FUs [185].…”
Section: Hemocyanin-derived Cryptidesmentioning
confidence: 99%
“…Hemocyanin antiviral activity has been attributed to glycosylated sites (27,32,51,52). It was previously suggested that hemocyanin carbohydrate chains interact with surface-exposed amino acid or carbohydrate residues of the viruses through van der Waals interactions (53). Despite hemocyanins having been found to be associated with arthropod antiviral immunity due to their increased expression upon viral infection (54,55) and the finding that their antiviral activity is effective against their own arthropod viruses (56,57), the role of hemocyanins in molluscan immunity remains unclear.…”
Section: Structures and Mechanisms Of Action Of Molluscan Antiviral Cmentioning
confidence: 99%